ISLAMIC EDUCATION MANAGEMENT AND THE FUTURE OF ARABIC LANGUAGE IN ISLAMIC PRIMARY EDUCATION: A CRITICAL REVIEW - Purwanto; Ahmadi; Sugeng Riyadi (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Arabic language education occupies a central position in Islamic primary education, not only as a medium for understanding religious texts but also as a foundation for Islamic intellectual and cultural formation. However, in many Islamic primary schools, particularly Madrasah Ibtidaiyah, Arabic learning continues to face structural and pedagogical challenges that hinder its effectiveness. This article critically examines the role of Islamic education management in shaping the future of Arabic language learning in Islamic primary education. Using a critical-conceptual approach supported by relevant literature, the study argues that the sustainability and quality of Arabic education at the primary level are not merely pedagogical concerns but are deeply rooted in managerial orientations, institutional priorities, and governance practices. The article highlights key managerial issues, including curriculum governance, leadership vision, teacher development, and learning culture, and proposes a reorientation of Islamic education management toward a more strategic, integrated, and future-oriented framework. This study contributes to the discourse on Islamic education by positioning management as a decisive factor in revitalizing Arabic language learning in Islamic primary education.